A pilot evaluation of a novel First Episode and Rapid Early Intervention service for Eating Disorders (FREED). (19th February 2018) - McClelland, Jessica; Hodsoll, John; Brown, Amy; Lang, Katie; Boysen, Elena; Flynn, Michaela; Mountford, Victoria A.; Glennon, Danielle; Schmidt, Ulrike
Abstract: This pilot study assesses the impact of FREED (First Episode Rapid Early Intervention for Eating Disorders [ED]), a novel transdiagnostic service for emerging adults with recent ED onset, on clinical outcomes. Data were collected from 56 patients and 19 carers for 12 months following enrolment. FREED patients showed significant improvements in ED and other symptoms across time. Carers also showed psychological improvements. For FREED anorexia nervosa (AN) patients, body mass index (BMI) at initial clinical assessment was similar to that of comparable patients (audit cohort) seen in our service before (16.4 vs 16.1 kg/m 2 ). By start of treatment, because of their shorter wait, FREED‐AN had gained weight whereas audit patients had lost (16.7 vs 15.8 kg/m 2 ). This difference continued throughout treatment, and at 12 months, nearly 60% FREED‐AN patients returned to a BMI of 18.5 or greater. FREED shows promise as a service model for emerging adults with EDs.